Semisynthetic Triazoles as an Approach in the Discovery of Novel Lead Compounds - Morais, Pedro A. B.; Francisco, Carla S.; de Paula, Heberth; Ribeiro, Rayssa; Eloy, Mariana Alves; Javarini, Clara Lirian; Neto, Álvaro Cunha; Júnior, Valdemar Lacerda (Current Organic Chemistry, 2021)
Historically, medicinal chemistry has been concerned with the approach of organic chemistry for new drug synthesis. Considering the fruitful collections of new molecular entities, the dedicated efforts for medicinal chemistry are rewarding. Planning and search for new and applicable pharmacologic therapies involve the altruistic nature of the scientists. Since the 19th century, notoriously applying isolated and characterized plant-derived compounds in modern drug discovery and various stages of clinical development highlight its viability and significance. Natural products influence a broad range of biological processes, covering transcription, translation, and post-translational modification, being effective modulators of most basic cellular processes. The research of new chemical entities through “click chemistry” continuously opens up a map for the remarkable exploration of chemical space towards leading natural products optimization by structure-activity relationship. Finally, in this review, we expect to gather a broad knowledge involving triazolic natural product derivatives, synthetic routes, structures, and their biological activities.
Keywords: Triazole